A clinical scoring system to predict the development of intraventricular hemorrhage (IVH) in premature infants - (:unkn) unknown (SPRINGER, 2018)
The aim of this study is to develop a scoring system for the prediction of intraventricular hemorrhage (IVH) in preterm infants in the first 7 days of life. A prospective, clinical study was conducted in Bahcesehir University, Medical Park Goztepe Hospital Neonatal Intensive Care Unit, with the enrollment of 144 preterm infants with gestational age between 24 and 34 weeks. All preterms were followed up for IVH after birth until the 4th week of life. The demographic characteristics and clinical risk factors were noted. Risk factors were analyzed. The score was established after logistic regression analysis, considering the impact of each variable on the occurrence of IVH within the first 7 days of life. The IVH scores were further applied prospectively to 89 preterm infants as validation cohort. Low gestational age (GA), low Apgar score, and having bleeding diathesis were the most important risk factors for IVH. According to these risk factors, a scoring system was developed for IVH ranged from 0 to 5. According to the risk ratios (RR) obtained from the logistic regression model, low GA (ae 28 gestational week), presence of bleeding diathesis within 7 days, and low Apgar score increased the risk of IVH (RR = 3.32 for GA ae 28 gestational week, RR = 6.7 for presence of bleeding diathesis in 7th day, RR = 3 for having low Apgar score). The score was validated successfully in 89 infants. The area under ROC curve was 0.85 for derivation cohort and 0.807 for validation cohort. The predictive ability of the IVH score for derivation and validation cohort was calculated. The negative predictive values of a score less than 4 were 96.4 and 59.1%. Concerning IVH-related sequelae which continue to be a major public health problem, we have developed a feasible predictive model for evaluating the risk for developing IVH for preterm infants in the first 7 days of life.
Keywords: Intraventricular hemorrhage; Preterm; Prediction; PRETERM INFANTS; RISK-FACTORS; POSTHEMORRHAGIC HYDROCEPHALUS; PREVENTION; INFARCTION; INDOMETHACIN; MANAGEMENT; RESERVOIR; THERAPY; MODEL